1994
DOI: 10.1093/tropej/40.5.285
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Small for Gestational Age Births in Ahmedabad, India

Abstract: Intra-uterine growth retardation is an important public health problem in many developing countries. The authors conducted a case-control study of low birth weight (LBW) in three teaching hospitals and a population survey in Ahmedabad city, India during 1987-1988. To identify and quantify risk factors for small for gestational age births, we divided the low birth weight and control infants into small for gestational age (SGA, n = 617) and appropriate for gestational age (AGA, n = 1851) using an Indian birth we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
3
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 0 publications
3
19
3
1
Order By: Relevance
“…Our ®nding that women with lower BMI gave birth to babies who were lighter and shorter and had smaller heads are similar to those of several studies which have examined the relationship between maternal size and foetal outcome (Stein and Susser, 1975;Pivalizza et al, 1990;Baqui et al, 1994;Mavalankar et al, 1994). Pivalizza et al (1990), found that among South African women, those who produced light for date infants were the same height as study controls but they weighed less, suggesting that weight-forheight was an important determinant of reduced fetal growth.…”
Section: Maternal Nutritional Status M Thame Et Alsupporting
confidence: 86%
See 1 more Smart Citation
“…Our ®nding that women with lower BMI gave birth to babies who were lighter and shorter and had smaller heads are similar to those of several studies which have examined the relationship between maternal size and foetal outcome (Stein and Susser, 1975;Pivalizza et al, 1990;Baqui et al, 1994;Mavalankar et al, 1994). Pivalizza et al (1990), found that among South African women, those who produced light for date infants were the same height as study controls but they weighed less, suggesting that weight-forheight was an important determinant of reduced fetal growth.…”
Section: Maternal Nutritional Status M Thame Et Alsupporting
confidence: 86%
“…Pivalizza et al (1990), found that among South African women, those who produced light for date infants were the same height as study controls but they weighed less, suggesting that weight-forheight was an important determinant of reduced fetal growth. In a study in India, low maternal weight was found to be the major risk factor for low birth weight (Mavalankar et al 1994), but maternal height was also a predictor of birth weight. This is not unexpected since short stature may well be a re¯ection of poor maternal nutrition during her growing years.…”
Section: Maternal Nutritional Status M Thame Et Almentioning
confidence: 96%
“…A study in India demonstrated that maternal anemia increased the risk of SGA. 44 ANC utilization, including number and gestational age at first visit were found to be associated with SGA in a Swedish study. 45 The strengths of the study include the relatively large sample size and the fact that the hospitals in which the study was conducted cater to large numbers of women of all socioeconomic status from Kumasi and surrounding regions.…”
Section: Discussionmentioning
confidence: 86%
“…The reasons given by the women for including these foods were related to the health of both the woman and her baby, as well as for a safe delivery. Mavalankar et al 23 found that 26% of women reported adding milk and milk products and 15% GLV to their diets.…”
mentioning
confidence: 99%